The Impact of Liquidity and Leverage on Return on Investment (Roi) in Consumer Goods Firms Listed on The Indonesia Stock Exchange From 2021 to 2024 - Hakim, Lukmanul; Hernawati, Euis (International Journal of Management and Business, 2025)
This study seeks to examine the impact of liquidity and leverage on return on investment (ROI) in consumer products companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The study utilizes a quantitative methodology, including an associative design. Samples were chosen using purposive sampling, focusing on active enterprises that regularly publish yearly financial statements and supply comprehensive ratio data. The data were examined with multiple linear regression utilizing JASP statistical software. The findings demonstrate that both liquidity and leverage concurrently exert a substantial influence on ROI. Leverage exerts a favorable and considerable influence on ROI; however, liquidity does not have a meaningful impact. The adjusted coefficient of determination (adjusted R²) of 26.3% indicates that the variance in ROI can be elucidated by the two independent variables. These data indicate that effective debt management has a greater impact on investment return performance than the company's liquidity status.